Fostering Moderate Character of Santri: Effective Hidden Curriculum Strategy in Islamic Boarding Schools - Salim, Nur Agus; Zaini, Mohammad; Wahib, Abd.; Fauzi, Imron; Asnawan, Asnawan (Nazhruna: Jurnal Pendidikan Islam, 2024)
This research aims to investigate the role of the hidden curriculum in fostering a moderate character among students at Al-Ilahiyyah Islamic Boarding School in Ngoro, Jombang. Utilizing a qualitative case study design, the research involves Kiai, Ustadz, and students as participants. Data were gathered through in-depth interviews, observations, and document analysis. The findings reveal that: (1) there are five critical components of the hidden curriculum at the boarding school that contribute to developing students' moderate character, namely congregational prayers, religious book study sessions, public speaking, discussions, student life, and daily social interactions; (2) these components embody core values of moderation such as balance, openness, tolerance, non-imposition of opinions, and harmonious coexistence in diversity; (3) through the processes of habituation and internalization of these values, students' characters increasingly reflect moderate qualities. Consequently, the hidden curriculum significantly contributes to enhancing the moderate character of students at the studied location, as demonstrated by the diversity that allows the boarding school community to coexist peacefully.